Nimotuzumab in Combination with Chemoradiation for Locally Advanced Head and Neck Squamous Cell Carcinoma Cancer Patients: A Single-Arm Observational Study - Sari, Sakinah Rahma; Rachman, Andhika (Writing Center IMERI FMUI, 2024)
Background: Head and neck squamous cell carcinoma (HNSCC) incidence is predicted to increase in 2030. Most patients with HNSCC are diagnosed as locally advanced (LA), with a worse prognosis even with combination therapy. Nimotuzumab, a humanized-antibody monoclonal against epidermal growth factor receptor (EGFR), was hypothesized to improve LA-HNSCC patients’ survival. This study evaluated the real-world efficacy of adding nimotuzumab to chemoradiation (CRT) in patients with LA-HNSCC survival. Methods:This single-arm retrospective study was conducted in Dr. Cipto Mangunkusumo General Hospital. Patients diagnosed with LA-HNSCC from October 21, 2009, to May 21, 2024 were included. The outcomes assessed were patients’ two-year overall survival (OS), two-year progression-free survival (PFS), and treatment toxicities. Results: From the total of 30 patients included in the analysis, 93.3% were alive, and 86.7% of patients survived disease progression at the end of the two-year observation. The most common side effects were toxicities against the salivary gland (32.7%), mucous lining (21.2%), and skin (30.8%). Conclusions:This single-arm real-world study demonstrated the exceptional efficacy and safety of nimotuzumab in combination with CRT.